Gender stereotypes and political leadership: A study of Malaysian secondary schools / Wan Farihah Ahmad Fahmy - Wan Farihah , Ahmad Fahmy (2020)
Gender inequality continues to be a pervasive problem in both developing and developed nations. While significant progress has been made towards achieving gender equality in many aspects in the recent decades, educational attainment remains an issue in many developing economies. Worldwide, various institutional barriers also continue to prevent women from achieving their fullest political, social, and economic agency. The Malaysian narrative on gender equality in education runs counter to conventional expectations. In the last three decades, girls and women in Malaysia have made significant strides in educational attainment. However, despite this gender gap in schooling favouring females, women continue to be underrepresented in political leadership in Malaysia. Possible explanations include socio-economic attitudes, influences, and deficiencies within the schooling system per se. This study investigates the latter possibility using primary data collected on 616 secondary school students and their class teachers and principals from 20 schools. It examines gender stereotypes in student attitude towards leadership (i.e. the belief that “men are better political leaders”) as a function of teacher gender, independent of the influence of socio-economic backgrounds of students. The study schools are sampled from four states - Kuala Lumpur, Negeri Sembilan, Perak, and Kelantan. Three findings follow from the multivariate regression models of student attitudes towards leadership: (i) the support for the statement “Men are better political leaders” is higher among boys; (ii)having a female teacher is a significant and positive predictor of student gender attitudes; and (iii) fixed attributes such as student’s race and gender matter significantly in explaining gender attitudes. This study shows that the influence of female teachers is not driven by gender of the school principal, gender belief of the teacher, sex orientation of the school and religious identity of the sample states. This is in line with findings from previous studies on gender attitudes in other nations. Implications for policies are discussed in the study.